2012
DOI: 10.1118/1.4762682
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning and dosimetric characteristics of TrueBeam system: Composite data of three TrueBeam machines

Abstract: The commissioning data indicated good consistency among the three TB-LINAC units. The commissioning data provided us valuable insights and reliable evaluations on the characteristics of the new treatment system. The systematically measured data might be useful for future reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
122
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 18 publications
15
122
0
2
Order By: Relevance
“…Although several studies have reported commissioning data for Varian TrueBeam accelerator (Varian Medical Systems, Inc., Palo Alto, CA), 1 , 2 , 3 , 4 to the best of the authors' knowledge, there are no reported data for Varian's stereotactic radiosurgery system (SRS) with conical collimators. This system utilizes seven conical collimators with diameters of 17.5 mm, 15.0 mm, 12.5 mm, 10.0 mm, 7.5 mm, 5.0 mm, and 4.0 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported commissioning data for Varian TrueBeam accelerator (Varian Medical Systems, Inc., Palo Alto, CA), 1 , 2 , 3 , 4 to the best of the authors' knowledge, there are no reported data for Varian's stereotactic radiosurgery system (SRS) with conical collimators. This system utilizes seven conical collimators with diameters of 17.5 mm, 15.0 mm, 12.5 mm, 10.0 mm, 7.5 mm, 5.0 mm, and 4.0 mm.…”
Section: Introductionmentioning
confidence: 99%
“…On gated treatments, the high dose rate can also be an advantage. Varian's flagship is called True Beam to honor the FFF modes 19 , 20 , 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the bending magnet, carrousel, and electron scattering foils have been redesigned, the primary collimator is thicker than in older units, and an antibackscatter foil has been added 1 , 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Chang et al, (1) Beyer, (2) and Glide‐Hurst et al (3) performed comparisons of select photon and electron fields from unmatched TrueBeam units; in the Beyer and Glide‐Hurst et al studies, the units were installed in different centers. All three studies found their respective machines to be in excellent agreement with one another, Beyer citing percent depth dose (PDD), profile, and output measurements to be reproducible between machines within 2%.…”
Section: Introductionmentioning
confidence: 99%